PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU CORPORATE INTERNET REPORTING - Adelia Susanto (Ma Chung Press, 2018)
This study was conducted to prove the influence of corporate characteristic and corporate governance on the timeliness of corporate internet reporting. This research uses variable of company type, profitability ratio, liquidity ratio, leverage ratio as firm characteristic variable and ownership structure, issuance of shares, and composition of board commissioner as corporate governance variable. This research also use control variable that is company size and age of listing. Hypothesis testing is done by using logistic regression. The sample used is 165 companies listed on Indonesia Stock Exchange in 2015 that have been selected based on some criteria. The result of this research is that variable of company type, profitability ratio, liquidity ratio, leverage ratio, ownership structure, issuance of shares and composition of board commissioner have no significant effect to the timeliness of corporate internet reporting. Based on the result of this study, it can be concluded that corporate internet reporting is voluntary disclosure. Therefore, the timeliness of corporate internet reporting is the authority of every company. In addition, the timeliness of corporate internet reporting is also influenced by the company’s various conditions. The results of this study can also mean that perhaps the timeliness of corporate internet reporting is caused by external factors of the company.